May macroglossia in COVID-19 be related not only to angioedema?. Issue 1 (January 2022) - Colombo, Daniele; Del Nonno, Franca; Nardacci, Roberta; Falasca, Laura
Abstract: SARS-CoV-2 infection can lead to a variety of clinical manifestations. The occurrence of tongue swelling has recently reported in severe cases of COVID-19, and angioedema has suggested as the causative mechanism. Several factors, such as genetic predisposing factor and angiotensin-converting enzyme inhibitors (ACEI) therapies, have proposed to induce angioedema, especially as concerns patients requiring ICU treatments. Nevertheless, the question is still debated and other causes not yet recognized should be considered. Here we present a case of macroglossia occurred in a patient deceased for COVID-19 disease, who had no family history of angioedema and did not receive ACEI as antihypertensive drug. Histological and immune-histochemical analysis revealed tongue muscle atrophy with infiltrating macrophages suggesting repair mechanisms, as seen in nerve injury recovery. These new pathological findings may open new fields of study on the pathogenesis of SARS-CoV-2.